The fifth estate - Camon, Ferdinando 1935-
The first of his three classic autobiographical novels, The Fifth Estate chronicles the passing in our own time of an ageless civilization, that of the peasant world Camon was born into. The trilogy--which also includes Life Everlasting and Memorial--has appeared in translation worldwide since its publication in the 1970s--From Amazon